Unveiling the synergetic benefits of the tunneling technique using stapler tractor in precise resection of lung segments: a retrospective cohort study - Zhu, Jian; Fu, Cheng-Hao; Chen, Liang; Zhu, Quan; Zhu, Shu-Sheng; Zheng, Jianan; Liao, Wei; Li, Kun; Wen, Wei (Frontiers in Oncology, 2024)
Background: Tunneling technique has shown preliminary promise in lung segmentectomy which requires the use of staplers in specific procedures.However, the obstacle when staples pass is the most obvious factor hindering the implementation and development of this technique. This study investigated whether the obstacle of the technology could be addressed by using an innovative self-designed stapler tractor and analyzed the combined and respective advantages of them.The clinical data of patients with lung nodules located near anatomical sites with potential tunnel creation treated by segmentectomy were analyzed in this retrospective case-control study. The data were divided into four groups according to four distinct surgical strategies: In Group A, the tunneling technique was performed with a stapler tractor; in Group B, the tunneling technique was performed without a stapler tractor; in Group C, didn't perform the tunneling technique but using stapler tractor in a normal approach; and in Group D, neither performed the technique nor used the stapler tractor. The general linear data, operation times, intraoperative adverse events, postoperative recovery and complications were compared.Compared with other groups, Group A exhibited the best surgical outcomes in comprehensive aspects. Separately, the tunnel groups (Group A&B) had better outcomes in the macro implementation of operation, including resection margin, the number of sampled intrapulmonary lymph nodes and resected subsegments, while the staple tractor groups (Group A&C) performed better on details of the procedure, including operation time, conversion to thoracotomy, and intraoperative bleeding (p < 0.05). Both of them were beneficial for shorter hospital stay, and the tunnel group was more advantageous.The tunneling technique is an advanced and beneficial surgical strategy for performing precise resection of lung segments while a stapler tractor can promote and facilitate it as a supplementary instrument. They show more combined benefits in effectively minimizing the occurrence of 3 / 18 erroneous injuries and enhancing the operational efficacy.